ONOMASTIC UNITS IN TOURISM TRANSLATION: A PRAGMATIC PERSPECTIVE - Akhmedjonova Nigora Tohirovna (International Journal of Literature and Language Studies, 2026)
This article examines onomastic units in tourism translation from a pragmatic perspective. It analyzes the role of proper names in conveying cultural meanings and facilitating intercultural communication. The study highlights the importance of preserving the pragmatic and cultural value of onomastic units in tourism discourse.